Economic Empowerment of Women Costumers Through the Future Package Program (PMD) At BTPN Syariah MMS, Tanjung Balai Selatan District - Dea Lora Veni; Fauzi Arif Lubis; Aqwa Naser Daulay (Journal of Management and Business Innovations, 2021)
Paket Masa Depan (PMD) financing product is provided by Bank BTPN Syariah to poor people, especially women, to empower underprivileged families to have a better life with Murabahah and Wakalah agreement. This research is the first to aim to analyze and describe the implementation of PMD at BTPN Syariah MMS, Tanjung Balai Selatan District. Second, to determine the impact on customers in Tanjung Balai Selatan District with PMD at Bank BTPN Syariah. The research approach used in this research is descriptive qualitative with data collection methods using observation, interviews, and documentation. The study results conclude that the first 90% of BTPN Syariah Bank has carried out the stages of financing requirements per the provisions. However, a less-than-optimal role of the companion is given by Bank BTPN Syariah (maintenance). Second, PMD has 80% positively impacts female customers' welfare in Tanjung Balai Selatan District to improve the economy of both families and communities. The Future Package program helps those who want to open a business and increase business capital. However, some customers have not felt the impact of PMD because of the less-than-optimal role of the companion given to them.Keyword: Community economic empowerment, murabahah, Paket Masa Depan (PMD), wakalah